PROGRAM BINA DESA DALAM PEMBERDAYAAN MASYARAKAT UNTUK PEMANFAATAN BUDI DAYA IKAN DALAM EMBER DAN AQUAPONIK ERA COVID-19 - Mochammad Maulidie Alfiannor Saputera; Noor Aisyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
In 2018 the village development program in the Tatah Layap Village was implemented. Activities carried out in 2020 include empowering the community in the cultivation of fish in buckets and aquaponics. This program aims to increase fishery resilience in supporting the community's economy. The program this time is to utilize catfish seeds and kale seeds. The community involved this time is the head of the household who comes from Tatah Layap Village. The number of participants in this activity was 22 people. The method used in this community service is a combination of community empowerment, training and mentoring for 3 days by involving students in 2020 village development program participants. The first step is making bucket containers in breeding catfish seeds which previously activated water media using EM4 for 2 days. Then prepare the materials needed in making aquaponics. Fish farming in buckets and aquaponics is maintained until the harvest process. The results show that the harvest of water spinach is once every 2 weeks within the period of spreading water spinach seeds once and harvesting catfish for 2 months.